2005
DOI: 10.1038/nature04252
|View full text |Cite
|
Sign up to set email alerts
|

A record of Permian subaqueous vent activity in southeastern Brazil

Abstract: The remarkable occurrence of more than 4,500 conical siliceous mounds in an area of less than 1.5 square kilometres has been reported in the Paraná basin, near Anhembi, São Paulo, in southeastern Brazil. These structures, which are up to two metres high, are thought to have been formed at the margin of a very shallow, broad but waning internal sea, and it was originally suggested that they are stromatolites. Yet their restricted occurrence, unusual abundance and nearly pure siliceous composition have never bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
21

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 9 publications
0
10
0
21
Order By: Relevance
“…No entanto, evidencias de hidrotermalismo e a presença de estruturas de deformacionais como sismitos e falhas sin-sedimentares nas formações Teresina, Rio do Rasto, Corumbataí e Piramboia indicam que a bacia estava sujeita a esforços tectônicos oriundos das margens de Gondwana (Riccomini et al 1992;Rostirolla et al 2000;Yamamoto et al 2005;Warren 2005). Diques clásticos que seccionam depósitos da Formação Serra Alta nas cercanias das cidades de Piracicaba (SP) confirmam a hipótese de que essa unidade se depositou sob influência de tectonismo ativo (Fig.…”
Section: Discussionunclassified
“…No entanto, evidencias de hidrotermalismo e a presença de estruturas de deformacionais como sismitos e falhas sin-sedimentares nas formações Teresina, Rio do Rasto, Corumbataí e Piramboia indicam que a bacia estava sujeita a esforços tectônicos oriundos das margens de Gondwana (Riccomini et al 1992;Rostirolla et al 2000;Yamamoto et al 2005;Warren 2005). Diques clásticos que seccionam depósitos da Formação Serra Alta nas cercanias das cidades de Piracicaba (SP) confirmam a hipótese de que essa unidade se depositou sob influência de tectonismo ativo (Fig.…”
Section: Discussionunclassified
“…This suggestion is evidenced by the specific vertical stacking occurrence that the quartz veins terminate immediately under the overlying bedded chert successions without upward penetration. Moreover, the characteristic textural and compositional features of these veins, which are analogous to the hydrothermal silica-barium deposits on the modern oceanic seafloor (Herzig et al, 1988;Urabe and Kusakabe, 1990;Stüben et al, 1994;Bogdanov et al, 1997;Bohrmann et al, 1999;Halbach et al, 2002;Hein et al, 2008) and ancient examples (Nijman et al, 1999;Yamamoto et al, 2005;Kiyokawa et al, 2006;Van Kranendonk, 2006;Chen et al, 2009;Wang et al, 2012), also suggest a subseafloor hydrothermal origin. In this case, the low-temperature, silicarich hydrothermal fluids were vented diffusively into the earliest Cambrian bottom seawater, promoting widespread deposition of the overlying bedded cherts in the basal Cambrian Yurtus Formation.…”
Section: Habitat and Fossilizationmentioning
confidence: 92%
“…Composition and textures of JR are similar to those of Permian siliceous mounds from southeastern Brazil, generated probably by subaqueous hydrothermal venting (Yamamoto et al, 2005), as well as to siliceous mounds formed by hydrothermal activity in shallow water at Yellowstone (Guidry and Chafets, 2003). Pokrovskii et al (2001) reported at several sites in the Tunguska region, including one less than 20 km from the TE epicenter, carbonate-magnetite deposits formed allegedly by hydrothermal alteration of Permian-Triassic Trap basalts.…”
Section: A Hydrothermal Origin?mentioning
confidence: 90%